Correction: Carvalho et al. Increased Cardiometabolic Risk in Dynapenic Obesity: Results from the Study of Workers’ Health (ESAT). Life 2024, 14, 1174 - Mariana de Oliveira Carvalho; Alice Pereira Duque; Grazielle Vilas Bôas Huguenin; Mauro Felippe Felix Mediano; Luiz Fernando Rodrigues Júnior (Life, 2025)
In the original publication, there was a mistake in Table 3 [...]